2012
DOI: 10.1136/postgradmedj-2012-131321
|View full text |Cite
|
Sign up to set email alerts
|

Foundation doctors’ views on whether their medical school prepared them well for work: UK graduates of 2008 and 2009

Abstract: Medical schools need feedback from their graduates about elements of medical school training that could improve preparedness for medical work. It also seems likely that there are some reasonably straightforward lessons that medical schools could learn from each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 14 publications
3
54
1
Order By: Relevance
“…For example, some asked a simple broad question such as “how well did your undergraduate course prepare you for examining patients”36 and provided five categories from ‘unprepared’ to ‘extremely well prepared’. Others provided a general statement such as “my experience at [medical school] prepared me well for the jobs I have undertaken so far”34 37 using five categories from ‘strongly agree’ to ‘strongly disagree’ or a scaled response from ‘generally not at all’ to ‘generally very well prepared’. Another approach required junior doctors to rate their preparedness for practice at the point of graduation (a more specific question) against curricula outcomes with a four-point scale from ‘poor’ to ‘very good’ 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some asked a simple broad question such as “how well did your undergraduate course prepare you for examining patients”36 and provided five categories from ‘unprepared’ to ‘extremely well prepared’. Others provided a general statement such as “my experience at [medical school] prepared me well for the jobs I have undertaken so far”34 37 using five categories from ‘strongly agree’ to ‘strongly disagree’ or a scaled response from ‘generally not at all’ to ‘generally very well prepared’. Another approach required junior doctors to rate their preparedness for practice at the point of graduation (a more specific question) against curricula outcomes with a four-point scale from ‘poor’ to ‘very good’ 38.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that the following factors influence higher self-ratings of preparedness: medical school,14 34–36 39 67 graduates from more recent cohorts,27 34 35 37 graduate-entry students,35 70 shadowing and other attachments,70 problem-based learning courses,27 70 UK-trained versus non-UK-trained graduates working in the UK,32 60 graduates with an intercalated degree35 and experience since starting work 70. Furthermore, there is some evidence that suggests that school is not a factor 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescribing is one of the most frequent activities undertaken junior doctors in UK hospitals, yet trainees often report that they feel underprepared to prescribe following completion of their undergraduate education [1317]. A study commissioned by the General Medical Council (GMC) found that trainee doctors prescribe with an average error rate of 10%, and concluded that training in practical prescribing should form part of undergraduate education [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such concern varies between students from different medical schools and is unrelated to how closely they consider that they are supervised in clinical settings. [5][6][7][8][9] A number of recent studies (most notably the GMC's EQUIP study) have raised questions about errors in prescribing by…”
mentioning
confidence: 99%